Cardiac Magnetic Resonance for Diagnosis of Neuroendocrine Tumor Metastases to the Right and Left Ventricles with Carcinoid Heart Disease. (5th December 2019) - Barnebee, Daniel; Morse, Brian; Strosberg, Jonathan R.; Pejic, Marijan; Jeong, Daniel
Abstract : A 76-year-old male with a small bowel neuroendocrine tumor with hepatic metastases presented with new onset lower extremity swelling, bloating, and weight gain which ultimately lead to cardiac magnetic resonance (CMR) to evaluate for cardiac involvement of disease. CMR showed right and left ventricular myocardial metastases along with findings suggestive of carcinoid heart disease. The patient had severe tricuspid valve regurgitation necessitating surgical valve repair. The patient underwent bioprosthetic tricuspid valve replacement and debulking of the metastases with surgical pathology confirming neuroendocrine tumor metastases. Follow-up clinical evaluations at 3, 6, and 9 months postoperatively showed improvement in cardiac function and stable hepatic tumor burden. This case demonstrates the utility of CMR to diagnose myocardial metastases and carcinoid heart disease complicated by severe tricuspid regurgitation, which guided surgical management.